HABILIDADES EMOCIONALES PERCIBIDAS EN ESTUDIANTES DE CARRERAS DE CIENCIAS DE LA SALUD EN HIDALGO, MÉXICO - Ruben García Cruz; Norma Angélica Ortega Andrade; Ana María Rivera Guerrero; Mucio Alejandro Romero Ramírez; Briztdy Benítez Martínez (European Scientific Journal, ESJ, 2013)
﻿﻿﻿Emotional intelligence as involved in the recognition process, use, understanding and management of own and others' emotional states, to resolve emotional problems and regulate behavior (Salovey, Brackett and Mayer, 2004), is taken up in this research, based in Model Mayer and Salovey (1990), in order to identify whether there were significant differences in perceived emotional skills that students have health sciences, with respect to discipline, sex and level of schooling path. The study included 236 university students from six disciplines of the Institute of Health Sciences at the Autonomous University of the State of Hidalgo, Mexico. The sample was selected based on a stratified probability sampling (J. García-García, G. García-García, Arnaud-Viñas, González-Martínez, Arámbula-Morales, y Mendoza-Guerrero, 2009). The quantitative study is design transectional. The instrument was administered TMMS-24. The results obtained in the multivariate analysis of variance, reported no statistically significant data by combining together the variables (disciplines, sex and level of schooling path) to the three dimensions of the instrument (attention, clarity and repair), differences were observed only within each variable with respect to size, these are presented in order to observe the behavior of perceived emotional skills in the sample of college students, as a reference for future research.